Getting to the Heart of the Matter: Exploring the Intersection of Cardiovascular Disease, Sex and Race and How Exercise, and Gut Microbiota Influence these Relationships - John J. Guers; Kevin S. Heffernan; Sara C. Campbell (Reviews in Cardiovascular Medicine)
Cardiovascular disease (CVD) is the leading cause of death worldwide, with physical inactivity being a known contributor to the global rates of CVD incidence. CVD incidence, however, is not uniform with recognized sex differences as well and racial and ethnic differences. Furthermore, gut microbiota have been associated with CVD, sex, and race/ethnicity. Researchers have begun to examine the interplay of these complicated yet interrelated topics. This review will present evidence that CVD (risk and development), and gut microbiota are distinct between the sexes and racial/ethnic groups, which appear to be influenced by acculturation, discrimination, stress, and lifestyle factors like exercise. Furthermore, this review will address the beneficial impacts of exercise on the cardiovascular system and will provide recommendations for future research in the field.